2011
DOI: 10.1159/000324931
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward Genetic Research Review: Results from a Survey of Human Genetics Researchers

Abstract: Background: Researchers often relate personal experiences of difficulties and challenges with Institutional Review Board (IRB) review of their human genetic research protocols. However, there have been no studies that document the range and frequency of these concerns among researchers conducting human genetic/genomic studies. Methods: An online anonymous survey was used to collect information from human genetic researchers regarding views about IRB review of genetic protocols. Logistic regression was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 38 publications
2
41
0
Order By: Relevance
“…Findings from this study provide evidence regarding current viewpoints of researchers in which a plan for disclosure of IRRs may be contingent on the genotyping method, medical significance of the specific finding, the participant preferences, and viewpoints of IRB chairs on need for guidance for disclosure of GIFs from genetic research studies. This evidence builds on the findings from Edwards et al (2011) in which return of results was not a common finding. Edwards et al also noted that those researchers who had served on IRBs were more likely to report positive consequences of IRB review.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Findings from this study provide evidence regarding current viewpoints of researchers in which a plan for disclosure of IRRs may be contingent on the genotyping method, medical significance of the specific finding, the participant preferences, and viewpoints of IRB chairs on need for guidance for disclosure of GIFs from genetic research studies. This evidence builds on the findings from Edwards et al (2011) in which return of results was not a common finding. Edwards et al also noted that those researchers who had served on IRBs were more likely to report positive consequences of IRB review.…”
Section: Discussionsupporting
confidence: 79%
“…When researchers were asked what they would do in response to hypothetical situations involving unexpected findings in genetic research, most stated they would disclose IFs, with their decisions governed by quality of information, adherence to rules, and research participant welfare (Meacham et al, 2010). However, only about one-third of researchers who were surveyed about IRB challenges regarding human genetic research identified return of IRRs to participants as an important issue (Edwards et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Opinions were more divided concerning such an obligation if a participant asked for results or if the researcher felt the participant might be interested. 8,9 The similarity of findings in studies from different countries suggests that researchers share common views. On the other hand, differences in opinions were found between Spanish and US researchers, 8 warranting caution in generalization of study results.…”
Section: Discussionmentioning
confidence: 99%
“…However, only few studies addressed their opinion on this issue. [8][9][10][11] We surveyed researchers involved in biobanks to study their opinions towards an obligation to return research results to participants and related issues such as ownership of blood samples, privacy, therapeutic relation, costs and implications for participants. …”
mentioning
confidence: 99%
“…[9][10][11][12][13] The ethical and legal appropriateness of different consent models is one of the most divisive topics with the absence of a consensus among academic scholars, 6 research policies, 14 and public opinion data. 15 While the bulk of research studies focus on capturing the perceptions of the general public and patients on research ethics issues related to biobanking, [16][17][18] only a few have focused on understanding the views of scientists who may manage biobanks [19][20][21][22][23][24][25] and even fewer concentrate on scientists' perceptions of informed consent. 26,27 It is important to capture the opinions of scientists as they run biobanks and are the end users of biorepository samples and information and thus have first-hand knowledge on biobank functions.…”
Section: Introductionmentioning
confidence: 99%